A study looking at different types of severe rashes called acute exanthemas. (3rd February 2020) - Deschamps, O.; Ortonne, N.; Hüe, S.; Rodriguez, C.; Deschodt, C.; Hirsch, G.; Colin, A.; Grégoire, L.; Delfau‐Larue, M.‐H.; Chosidow, O.; Wolkenstein, P.; Ingen‐Housz‐Oro, S.
Summary: Severe rashes, called acute exanthemas (AE), are frequently seen in hospital. The most common type is called maculopapular exanthema (MPE), and another type is pityriasis rosea. The main causes of AEs, especially MPEs, are drugs (delayed hypersensitivity) and viruses (such as HIV, human herpesvirus 6 ‐ HHV6, and measles virus), but for some no cause is identified, which is known as ideopathic. There are no guidelines for which tests (viral investigations) should be carried out. The researchers conducted this study to better describe AE, and to explore the value of investigations into the causes of AE, called cytokinic and metagenomic analysis. 98 patients being seen at the Henri Mondor hospital in France were included. Patients were examined by a medic, received tests for viruses, and skin biopsies (tissue samples) were taken. Patients were classified into five groups: viral group (18 people), drug‐induced group (33), drug‐induced and viral (5), idiopathic (32) and pityriasis rosea (10). HHV6 was the most common virus found (74%). Analysis looking at levels of proteins called cytokines showed higher levels of a cytokine called interleukin‐33 in the idiopathic exanthemas (i.e. the ones with an unidentified cause). This could suggest an environmental factor as a trigger. The study showed for the first time the feasibility of metagenomics analysis (studying the genetic material) in the skin, and the results question whether some of the routine virus tests used are always beneficial. This summary relates to the study: Acute exanthemas: a prospective study of 98 adult patients with an emphasis on cytokinic and metagenomic investigation Abstract : Linked Article:  Deschamps et al. Br J Dermatol 2020; 182 :355–363